Governance Arrangements for the Scaling Up of Small-Scale Wastewater Treatment and Reuse Systems – Lessons From India - Reymond, Philippe; Chandragiri, Rohit; Ulrich, Lukas (Frontiers in Environmental Science, 2020)
Environmental pollution and increasing water scarcity are key features of the urban landscape of India today. The extension of centralised sewerage networks cannot keep up with city growth, and alternative sanitation systems are needed for citywide inclusive sanitation (CWIS). The government of India mandated larger buildings to be equipped with small-scale wastewater treatment plants (SSTP). This resulted in the emergence of a large number of technology and service providers, and in the implementation of thousands of private SSTPs. However, this quick scaling up was not accompanied by the development of appropriate governance arrangements. As a result, a significant proportion of SSTPs underperform and do not meet the effluent standards. Through a systematic analysis of governance arrangements around SSTPs, this contribution analyses the scaling up process of small-scale wastewater management and reuse at building level in India, in particular in the state of Karnataka and the city of Bengaluru. This paper identifies the gaps in this multi-level, polycentric governance framework and investigates which arrangements are needed to enable the performance of SSTPs on the ground and to create the necessary synergies between the relevant governmental agencies, the private sector and civil society. The scaling up of SSTPs in India mainly followed a market governance approach within a governance environment that is traditionally very hierarchical. The authors argue that hybrid governance arrangements, blending hierarchical, market and network governance are needed to foster market regulation and stakeholder coordination, and increase the performance of the sector. They conclude that an efficient governance of SSS requires the creation of dedicated SSS units at state and city level, and the development of an online platform collating all databases, streamlining and supporting processes from establishment to monitoring, and allowing meaningful collaboration between stakeholders. Through the case study of India, this paper contributes to understand the governance arrangements necessary for the successful scaling up of decentralised sanitation systems, and how to fulfil the potential of alternative solutions for sustainable urban water management. It contributes to governance studies by substantiating the concept of hybrid governance approach and proposing concrete measures to make it work for such distributed systems.